ANALISIS BIAYA PRODUKSI DALAM PENETAPAN HARGA JUAL DIGITAL PRINTING PADA CV. FORTUNNAADVERTISING KOTA BENGKULU - Suwarni, Suwarni; Kaulan, Kaulan; Yanopi, Sahridi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2019)
This study aims to determine the production cost with a full costing method and fixed selling price using cost plus pricing method on the CV. Fortunna advertising bengkulu city in 2015 through 2017. The research method is manifold diskkriptif and methods of data collection using observation and documentation. From the calculation of cost of production by using the full costing method with each of the expected profit of 30% so as to obtain the cost of production for the banner in 2015 that the cost of production amounted to Rp.17.587,- profit planning for Rp.5.276,- ​​and setting the selling priceRp. 22.863.- in 2016 the cost of production amounted to Rp.17.637,- profit planning for Rp.5.301 and setting the selling price amounted to Rp.22.938,- whereas in 2017 the cost of production amounted to Rp.17.852,- planning  profit of Rp. 5.355,- selling price of Rp. 23.207,-. For the production of billboards permeter in 2015 the cost of production amounted to Rp.20.040, - profit planning for Rp.6.012,- and setting the selling price amounted to Rp.26.052,- in 2016 the cost of production amounted to Rp.20.008,- planning a profit of .Rp.6.002,- and setting the selling price of Rp.26.010,- whereas for 2017 the cost of production amounted to Rp.20.168,- profit planning for Rp.6.050,- and setting the selling price amounted to Rp.26.218,-.  Thus showing that CV. Advertising Fortunna preformance produce goods has  calculated the costs of production accordingly.